Adaptation Strategies Of Octopus Fishermen In Linau Village Maje Subdistrict Kaur Regency To Climate Changes Impacts - Nyayu Neti Arianti; Nurul Hafiza; Andi Irawan (UNIVED Press, Dehasen University Bengkulu, 2025)
The Purpose : This study aims to analyze the impacts of climate change felt by octopus fishermen in Linau Village, Maje District, Kaur Regency along with the adaptation strategies carried out for these impacts. Methodology : This case study research on octopus fishermen in Linau Village was conducted in October 2023 with 17 respondents taken through a census. Data were analyzed descriptively quantitatively. Results: The impacts of climate change felt by octopus fishermen include: decreasing octopus catches (100%), rising sea levels (82%), increasing sea temperatures (76%), increasing extreme weather events (65%), and increasing high wave intensity (59%). Adaptation strategies implemented by octopus fishermen, namely: finding sources of income in the on-farm fisheries sector other than octopus (94%), finding sources of income in the off-farm and non-fisheries fisheries sector (82%), adjusting fishing hours (53%), mobilizing family members to work (47%), utilizing social networks by borrowing (41%), and moving fishing areas (41%). Findings : Octopus fishermen in Linau Village quickly adapted and implemented different strategies compared to other areas, namely changing the octopus fishing hours. Novelty : This study was conducted on octopus fishermen in Linau Village where the strategies implemented were based on local resources and culture. Originality : This study uses the latest data from interviews and observations. Similar research has never been conducted before. Conclusion : Octopus fishermen in Linau Village feel various impacts of climate change and implement several strategies to adapt to these impacts. The development of more diverse alternative octopus processing businesses and the creation of non-octopus jobs need to be carried out in Linau Village. Type of Paper: Empirical Research Article.